2023
DOI: 10.1021/acs.molpharmaceut.2c00880
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Intratibial Osteosarcoma Using Water-Soluble Copolymers Conjugated to Collagen Hybridizing Peptides

Abstract: Osteosarcoma (OS) is the most common form of primary malignant bone cancer in adolescents. Over the years, OS prognosis has greatly improved due to adjuvant and neoadjuvant (preoperative) chemotherapeutic treatment, increasing the chances of successful surgery and reducing the need for limb amputation. However, chemotherapeutic treatment to treat OS is limited by off-target toxicities and requires improved localization at the tumor site. Collagen, the main constituent of bone tissue, is extensively degraded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Since local injection is a better drug delivery route for managing OA, and fast clearance in the joint is a known problem for IA therapeutics used in OA treatment, we investigated CHP binding to joint tissues after IA injection for the first time. Since CHP can be readily conjugated to drug molecules 16 and drug delivery systems for enhanced accumulation in pathological sites with high collagen degradation, 31,32 extended retention of CHPs in the joint tissue could potentially be applied to extending the efficacy of IA OA drugs. CHP retention was tested by in vivo imaging of rat knees after IA injection of NIRF‐labeled CHPs (Figures 1–2).…”
Section: Discussionmentioning
confidence: 99%
“…Since local injection is a better drug delivery route for managing OA, and fast clearance in the joint is a known problem for IA therapeutics used in OA treatment, we investigated CHP binding to joint tissues after IA injection for the first time. Since CHP can be readily conjugated to drug molecules 16 and drug delivery systems for enhanced accumulation in pathological sites with high collagen degradation, 31,32 extended retention of CHPs in the joint tissue could potentially be applied to extending the efficacy of IA OA drugs. CHP retention was tested by in vivo imaging of rat knees after IA injection of NIRF‐labeled CHPs (Figures 1–2).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the CHPs can be used to detect bone remodeling activity during development and disease progression, , mechanical damage to collagen in tendons, , invasive cancer, fibrosis, and other pathologies (Figure B). Due to their simple chemical structure, the CHPs can even be conjugated to either small molecules or macromolecules for localizing therapeutics to inflamed tissues (Figure B). These striking properties of CHPs are made possible by two key aspects of the CHPs. First, CHP hybridization relies not on the conventional protein–epitope binding mediated by side chain interactions of folded protein but on the formation of the secondary protein structure of the protein backbone.…”
Section: From Collagen Mimetics To Collagen Hybridizationmentioning
confidence: 99%